2020
DOI: 10.1021/acs.analchem.0c03991
|View full text |Cite
|
Sign up to set email alerts
|

Distance-Dependence Study of Plasmon Resonance Energy Transfer with DNA Spacers

Abstract: Plasmon resonance energy transfer (PRET) in hybrid plasmonic−molecular systems has a broad range of applications from catalysis to analytical/biochemical/biophysical imaging and sensing. Herein, we experimentally and theoretically probed the influence of the distance (d) between the plasmonic nanoparticle and the conjugated molecules on the PRET efficiency (η PRET ) using two PRET systems, which involved tetramethylrhodamine (TAMRA) or Cy3 molecules as acceptors and single spherical gold nanoparticles (AuNPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Both the experimental and quasi-static approximation data showed that η PRET displayed a d -value-dependent decay function. This research provided systematic insights into the widely used PRET technique …”
Section: Accurate Analysis Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the experimental and quasi-static approximation data showed that η PRET displayed a d -value-dependent decay function. This research provided systematic insights into the widely used PRET technique …”
Section: Accurate Analysis Applicationmentioning
confidence: 99%
“…This research provided systematic insights into the widely used PRET technique. 54 Plasmon Ruler. Another powerful tool in the iDFM is the plasmon ruler, which is based on the plasmon resonance coupling effect.…”
mentioning
confidence: 99%
“…In this way, the “loading-type” plasmonic nanosensor could realize the ONOO − determination with good selectivity and sensitivity (at a single nanoparticle level). Since PRET has broad applications in biosensing, the effect of the distance (d) between the conjugated molecules and the plasmonic nanoparticle on the PRET efficiency (ηPRET) has been investigated by utilizing Cy3 molecules or tetramethylrhodamine as acceptors and single spherical AuNPs as donors [ 53 ]. Double-stranded DNA was applied to regulate the d -values between the donor and the acceptor.…”
Section: Plasmonic Gold Nanostructures For Biosensing In Vitromentioning
confidence: 99%
“…[ 188 ] Furthermore, Ma and coworkers experimentally and theoretically probed the influence of the distance ( d ) between the PNP and the conjugated molecules on the PRET efficiency, and found that the PRET efficiency displayed a d ‐value‐dependent decay function. [ 189 ] Therefore, the quenching efficiency of PRET can be regulated by changing the distance between PNPs donor and molecules acceptor, indicating the applicability of the turn‐on and turn‐off types of sensing mechanisms. Liu and coworkers utilized quantum dots (QDs)‐AuNPs pair, in which PRET occurred from AuNPs to QD 800, to develop separation‐free homogeneous immunoassays for quantifying PSA (Figure 6C).…”
Section: Single Plasmonic Nanoprobes In Protein Determinationmentioning
confidence: 99%